Optimization of the use of carbon paste electrodes (CPE) for electrochemical study of the chalcopyrite - Horta, Daniela G. [UNESP]; Bevilaqua, Denise [UNESP]; Acciari, Heloisa Andréa [UNESP]; Garcia Júnior, Oswaldo[UNESP]; Benedetti, Assis Vicente [UNESP] (Sociedade Brasileira de Química, 2009)
The use of carbon paste electrodes (CPE) of mineral sulfides can be useful for electrochemical studies to overcome problems by using massive ones. Using CPE-chalcopyrite some variables were electrochemically evaluated. These variables were: (i) the atmosphere of preparation (air or argon) of CPE and elapsed time till its use; (ii) scan rate for voltammetric measurements and (iii) chalcopyrite concentration in the CPE. Based on cyclic voltammetry, open-circuit potential and electrochemical impedance results the recommendations are: oxygen-free atmosphere to prepare and kept the CPE until around two ours, scan rates from 10 to 40 mV s-1, and chalcopyrite concentrations > 20%.
Keywords: carbon paste electrodes (CPE); chalcopyrite; leaching